Pseudohalide‐Exchanged Quantum Dot Solids Achieve Record Quantum Efficiency in Infrared Photovoltaics. Issue 27 (10th May 2017) - Sun, Bin; Voznyy, Oleksandr; Tan, Hairen; Stadler, Philipp; Liu, Mengxia; Walters, Grant; Proppe, Andrew H.; Liu, Min; Fan, James; Zhuang, Taotao; Li, Jie; Wei, Mingyang; et al.
Abstract : Application of pseudohalogens in colloidal quantum dot (CQD) solar‐cell active layers increases the solar‐cell performance by reducing the trap densities and implementing thick CQD films. Pseudohalogens are polyatomic analogs of halogens, whose chemistry allows them to substitute halogen atoms by strong chemical interactions with the CQD surfaces. The pseudohalide thiocyanate anion is used to achieve a hybrid surface passivation. A fourfold reduced trap state density than in a control is observed by using a suite of field‐effect transistor studies. This translates directly into the thickest CQD active layer ever reported, enabled by enhanced transport lengths in this new class of materials, and leads to the highest external quantum efficiency, 80% at the excitonic peak, compared with previous reports of CQD solar cells. Abstract : Pseudohalogens in solar cells are applied and the performance is increased by reducing trap densities and implementing thick colloidal quantum dot (CQD) films. The pseudohalide‐exchanged CQD films have four times lower trap state density than the controls, as seen in field‐effect transistor (FET) studies. This results in an external quantum efficiency of 80% at the infrared excitonic peak, the highest reported in CQD photovoltaics.